HUBUNGAN PERILAKU KESEHATAN GIGI ORANG TUA TERHADAP STATUS KESEHATAN ANAK KEDUA MEREKA : STUDI KASUS DI SDLB ABC SWADAYA, KALIWUNGU, KENDAL - Sadimin Sadimin; Endah Aryati Eko Ningtyas; Yodong Yodong (Jurnal Kesehatan Gigi, 2018)
TITLETHE RELATION OF PARENTS’ BEHAVIOUR ON DENTAL HEALTH TOWARD THEIR DEAF CHILDREN’S ORAL HEALTH STATUS: CASE STUDY IN SDLB ABC SWADAYA KALIWUNGU KENDALABSTRACTThe Growth and the development of deaf children often cause the health problems, one of the problem is oral health. Factors that affect the level of oral health are knowledge, attitude and action. The deaf children dental health is influenced by the parents’ behavior to maintenance of oral health. The purpose of this research was to describe the relation of knowledge, attitudes and actions of parents about dental and oral health on dental health status of the deaf children.        The research method is observational analytic, with cross sectional research approach. The samples in this research was 30 people, it was total sampling for sampling technique. It was univariate analysis, bivariate analysis (chi square) and multivariate analysis (logistic regression) for data analysis.The results of statistical tests showed that parent’s knowledge, attitudes and actions about dental and oral health have a significant relation with dental and mouth health status (DMF-T) of the deaf children, with p-value 0,003 (p 0.05). The most related variable with dental and mouth health status (DMF-T) in deaf children is the attitude was p = 0.002. The conclusion of this research is parent’s knowledge, attitudes and actions about oral and dental health related to dental and mouth health status (DMF-T) of the deaf children. Attitude is the most related variable to dental and mouth health status (DMF-T).